Beverage Sales and Drinking and Driving: The Role of On-Premise Drinking Places - Gruenewald, P.; Stockwell, Tim; Beel, A.; Dyskin, E. (1999)
Objective: The relationships between on-premise drinking places, beverage specific alcohol sales and drinking and driving were examined in a time series cross-sectional study of place-of-last-drink data from Perth, Western Australia. Method: At arrest, 2,411 drinking drivers reported their last location of consumption. Tabulated by 57 premises over 4 years, the rates at which individual premises were referenced as the place-of-last-drink were taken to reflect the relative distributions of numbers of drinking drivers coming from different premise types (hotels, taverns and nightclubs. The data were then statistically related to measures of premise types and characteristics and beverage specific alcohol sales. Results: Significant cross-sectional relationships were obtained between measures of premise types, alcohol sales and drinking and driving. Greatest numbers of drinking drivers came from taverns and from places selling greater amounts of beer and spirits. Significant longitudinal effects were obtained for sales of beer, proportions of high alcohol beer sold and sales of spirits. Conclusions: As a whole, the results suggest that, at least for Western Australia, outlets selling greater amounts of beer and spirits, and greater amounts of high alcohol beer, will produce larger numbers of drinking drivers. (J Stud. Alcohol 60: 47-53, 1999)